Inklusi Teloghy : antara agama dan teknologi dalam perspektif Nauqib al-Attas - Diva Try Syafrielia; Khoirun Nisa Alhabibah; Lisa Qotrun Nandini; Septy Oktavia (At-Tuhfah : Jurnal Studi Keislaman, 2022)
The relationship between religion and technology is an important topic in the study of religion and technological development. Nauqib, a muslim scientist, provides a unique perspective on this matter. Nauqib realizes thet technology can make it easier to worship and spread religious messages, but he also realize that technology can have a negative impact on moral and spiritual values. Nauqib emphasizes the importance of education and awareness of technological ethics for muslim, so that they can utilize technology for good and not become slaves to technology. Nauqib also highlights the importance of the involvement of religious scholars and leaders in technology development. Nauqib’s perspective underscores the importance of harmony between religion and technology. Technology can be useful tool for muslims in strengthening religious practice and improving quality of life, provided it is used wisely and does not violte religious principles.